Srčni spodbujevalniki pri dojenčkih in otrocih - Kosin, Miro (Zdravniški vestnik, 2005)
Background. To review retrospectively our experience with pediatric cardiac pacing with an emphasis on specific problems in pacemaker implantation in infants and children. Methods. Between April 1977 and March 2005 ninety-one child underwent permanent pacemaker implantation, 46 boys (50.5%) and 45 girls(49. 5) with a mean age of 7.9 years (the oldest 17 years and the youngest 1 day). The age of the children at the time of implantation was 2 to 9 years in one half and 14 to 17 years in one fourth of them. Five children were younger than one month and three of them younger than one week. The indications for permanent pacing were complete atrioventricular block (CAVB) in more than half patients, sick sinus syndrome in one fourth and CAVB following open heart surgery in nine. The mean time for elective battery replacement was 6.5 years after the implantation. In one third of the childrenthe battery was replaced before the end of the fifth year after the implantation and after seven years in more than half of the patients. Epicardial leads and left anterior thoracotomy or subxyphoid approach were used at the beginning. From the year 1980 we prefered transvenous leads. Modern epicardial steroid-eluting leads demonstrated relatively stable acute and chronic pacing and sensing tresholds. WI/R pacemaker was the, pacemaker ofchoice at the first implantation and we upgraded the pacing at the time of the elective battery replacement. Children with VDD pacemakers needed sometimes upgrading of pacing sooner because of the inappropriaate atrial sensing and AV synchronyzation. Conclusions. Better quality pacing leads and smaller but more powerful pacemaker generators with autocapture-controlled pacing options became more and more attractive for our little patients becauseof better impluntation facilities, substantial energy savings and battery life prolongation.
Keywords: Cardiac Pacing, Artificial; Child; Dojenček; Heart Block; Heart Defects, Congenital; Infant; Instrumentation; Methods; Otrok; Srce, blok; Srce, napake prirojene; Srčno vzpodbujanje, umetno; Treatment Outcome; Zdravljenje, izid